Comprehensive Strategies and Emerging Trends in the Global Fight Against Malaria (International Journal of Life Sciences Biotechnology and Pharma Sciences, 2024)
Malaria remains a significant global health challenge, particularly in regions wherepoverty, climate, and limited access to healthcare converge. This review article provides acomprehensive overview of current research findings, control strategies, and emerging trends inthe fight against malaria. Drawing from a wide range of scientific literature and field reports, wedelve into the intricate web of factors influencing malaria transmission, its impact on communities,and the innovative approaches being employed to combat this ancient scourge. By synthesizingkey insights and highlighting gaps in knowledge, this review aims to inform policymakers,healthcare professionals, and researchers on the ongoing battle against "Malrira."